PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, PROMOSI, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN (STUDI PADA PEMBELIAN PRODUK ROKOK ELEKTRIK DI RAY VAPESTORE JUWANA) - Hendro Wibowo, 13.05.51.0066 (Students Journal of Economic and Management, 2017)
This study aims to analyze empirically the product quality, price perception, and promotion to the buyers purchase decision process electric cigarette products in Ray Vapestore Juwana. The population in this study are all consumers in Ray Vapestore Juwana. Sampling was done by using the formula method Slovin and the number of samples to be processed into the research data of 100 questionnaires. Data were analyzed using multiple linear regression model. The results showed that the quality of products, the perception of price, promotion and and location significantly positive influence the purchase decision of consumers to buy products at Ray vapestore Juwana. Keywords: Product Quality, Perceived Price, Promotion, location and Purchase Decision Process